A Wearable Strain Sensor Based on 3D Silicone Printing with Composite Structure Design - Lin, Jiun-Hung (International Journal of Online and Biomedical Engineering (iJOE), 2026)
Flexible strain sensors hold significant potential in wearable electronics and human motion tracking; however, achieving a balance among sufficient measurement range, low hysteresis response, and reliable skin adhesion remains challenging. In this study, a wearable strain sensor was developed using 3D-printed silicone, and the performance of a single-layer conductive silicone design (P1) was compared with a multilayer configuration integrating an adhesive interface and medical-grade artificial skin (P2). Results show that P2 successfully extends the measurable displacement range to 10 mm and reduces hysteresis from 0.26 to 0.03 at 3 mm strain, while maintaining stable cyclic performance (standard deviation ± 0.018). The multilayer architecture improves repeatability under repeated stretching by stabilizing the conductive network and enhancing skin-attachment reliability. Human testing further demonstrates that P2 can reliably track wrist motion within 0°–30°, with resistance changes closely aligned to IMU-derived angle signals and without noticeable baseline drift. Overall, this work presents a cost-effective, skin-compatible silicone strain sensor suitable for wearable human motion monitoring, highlighting its potential for applications in health tracking and rehabilitation-related movement analysis.